Absolute and relative changes in the consumer price index - Cerda Hernández, José (2020)
This work estimates a dynamic factor decomposition for Peruvian inflation, using monthly disaggregated data from the consumer price index of Metropolitan Lima from January 2000 to December 2019. One of the objectives of macroeconomics is to explain the aggregate sources of changes in the prices of goods in an economy. This model makes it possible to identify idiosyncratic relative prices, aggregate relative prices and absolute prices, which represent the supply and demand shocks that can appear in an economy. The component common to all items of the CPI serves as an alternative measure of core inflation, and our results show that this component is highly correlated with core inflation published by the BCRP. In general, the results obtained in the present work are robust for different intertemporal dependency structures for the factors considered. This work estimates a dynamic factor decomposition for Peruvian inflation, using monthly disaggregated data from the consumer price index of Metropolitan Lima from January 2000 to December 2019. One of the objectives of macroeconomics is to explain the aggregate sources of changes in the prices of goods in an economy. This model makes it possible to identify idiosyncratic relative prices, aggregate relative prices and absolute prices, which represent the supply and demand shocks that can appear in an economy. The component common to all items of the CPI serves as an alternative measure of core inflation, and our results show that this component is highly correlated with core inflation published by the BCRP. In general, the results obtained in the present work are robust for different intertemporal dependency structures for the factors considered.